1994
DOI: 10.1007/s002620050125
|View full text |Cite
|
Sign up to set email alerts
|

Different pattern of T cell receptor ? gene rearrangement in tumour-infiltrating lymphocytes and peripheral blood in patients with solid tumours

Abstract: Tumour-infiltrating lymphocytes (TIL) and peripheral blood lymphocytes (PBL) from four patients with renal-cell carcinoma (three paired with blood), two colon carcinomas (both paired with blood) and two melanomas (blood was not available) were analysed for the T cell receptor (TCR) delta gene repertoire. Polymerase chain reaction analysis, employing a panel of specific primers for TCR delta gene segments, showed different gene rearrangement patterns in TIL and PBL in all patients. Simultaneous analysis of TIL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Recent reports demonstrated that γδ T cells play a role in repair of damaged intestinal epithelial cells 5,6) and have the capacity to recognize certain antigens, such as special antigens on the surface of tumor cells and some superantigens, and that their cytotoxic activity is enhanced by TNFα. [15][16][17][18][19] Notably, it was reported that Vδ1-γδ T cells, which are predominant in the human intestinal mucosa, recognized the major histocompatibility antigen-related molecules, MICA and MICB, which are expressed on the surface of intestinal epithelial cells. The expression of the molecules was enhanced in colon tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports demonstrated that γδ T cells play a role in repair of damaged intestinal epithelial cells 5,6) and have the capacity to recognize certain antigens, such as special antigens on the surface of tumor cells and some superantigens, and that their cytotoxic activity is enhanced by TNFα. [15][16][17][18][19] Notably, it was reported that Vδ1-γδ T cells, which are predominant in the human intestinal mucosa, recognized the major histocompatibility antigen-related molecules, MICA and MICB, which are expressed on the surface of intestinal epithelial cells. The expression of the molecules was enhanced in colon tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The exact role of Vγ1 and Vδ1 TCR + cells in tumour immunology has still to be defined; however, γ/δ TCR + cells may be stimulated to secrete lymphokines and may act as activated killer cells and exert some cytolytic activity on several tumours 1. Extending earlier porcine7 and human6 28 reports on the existence of these cells in melanomas and the occurrence of spontaneous regression of melanomas,11 patient survival was analysed with respect to the infiltration by these cells. Interestingly, a highly significant positive correlation for survival could be defined.…”
Section: Discussionmentioning
confidence: 99%
“…γ and δ TCR + cells have been detected to selectively accumulate or to be amplified in non-ocular solid melanomas and are thought to indicate a unique type of host reaction against the tumour 6. Furthermore, tumour infiltrating cells expressing the γ and δ TCR + CD3 + complex have been found crucial for spontaneous regression of inheritable melanomas in the Sinclair miniature swine 7…”
mentioning
confidence: 99%
“…Preferential expansion and antitumor responses of subsets of γ/δ TILs have been found in many kinds of cancer, including colorectal cancer [4, 5], lung adenocarcinoma [6, 7]and pancreatic cancer [8]. Such γ/δ T cells demonstrated a non–MHC–restricted recognition and cytolytic activity to autologous/allogeneic tumor cell lines.…”
Section: Introductionmentioning
confidence: 99%